Efektivitas Model Pembelajaran Group Investigation Bervisi SETS Terhadap Literasi Sains Siswa - Suryaningsih, Yeni (Papanda Publisher, 2025)
This study aims to improve students' scientific literacy through the SETS visionary investigation group learning model. The learning design uses a pretest-posttest control group design. The data collection technique is descriptive quantitative with a hypothesis test using the nonparametric Two Independent Sample Test, namely the Mann-Whitney test. The results of the study showed that there was an increase in scientific literacy through the SETS visionary investigation group learning model as evidenced by the results of the Mann-Whitney U hypothesis test with (Sig. 2-tailed) 0.000 <0.05. The results of the recapitulation of observations of student activities using the SETS visionary investigation group learning model are included in the very good category. Keywords: Group Investigation Learning Model, SETS Approach, Science Literacy